2016
DOI: 10.1089/hs.2015.0060
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Community Assessment for Public Health Emergency Response to Wildfire, Bastrop County, Texas

Abstract: On September 4, 2011, a wildfire ignited in Bastrop County, Texas, resulting in losses of 34,068 acres of land and 1,645 homes and 2 deaths. At the request of the Texas Department of State Health Services Health Service Region 7 and the Bastrop County Office of Emergency Management, Community Assessments for Public Health Emergency Response (CASPER) were conducted in the weeks following the wildfire and again 3.5 years later to assess both the immediate and long-term public health and preparedness impacts of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…These findings suggest that the wildfire had significant adverse effects on the mental health of adolescents in Fort McMurray due to the traumatic nature of disasters. These results are consistent with the literature which reports a negative impact of wildfire disasters on mental health [7, 9, 10, 12–15, 3942]. These findings emphasize the need for mental health policies, programs, and supports specifically targeted to adolescents following disaster in order to reduce their vulnerabilities and build positive mental health.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings suggest that the wildfire had significant adverse effects on the mental health of adolescents in Fort McMurray due to the traumatic nature of disasters. These results are consistent with the literature which reports a negative impact of wildfire disasters on mental health [7, 9, 10, 12–15, 3942]. These findings emphasize the need for mental health policies, programs, and supports specifically targeted to adolescents following disaster in order to reduce their vulnerabilities and build positive mental health.…”
Section: Discussionsupporting
confidence: 91%
“…After wildfires, children and adolescents exhibit increased incidence of post-traumatic stress disorder (PTSD) and depression [7, 8]. Studies conducted with both adults and children/adolescents report that both have an increased incidence of PTSD [9] as well as increased symptoms of depression and stress [10]. Studies focusing only on adults show that they exhibit increased symptoms of depression and anxiety [11, 12], increased incidence of PTSD [11, 13], increased levels of psychological distress [14], and increased consumption of anxiolytics-hypnotics [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also reported links between wildfires and adverse mental health effects in adults and children, including increased symptoms of PTSD (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), increased symptoms of depression and anxiety (17,19,(23)(24)(25)(26)(27)(28), mental health difficulties (18,29,30), reduction in health and wellbeing (31), increased consumption of anxiolytics-hypnotics (32), and decreased capacity to cope with adversity (33). The combined adverse impacts of wildfire disasters on individuals' mental health and coping abilities, particularly in youth, are important because coping plays a major role in post-disaster recovery, and lack thereof can be detrimental to long-term mental health outcomes [also see (34)].…”
Section: Introductionmentioning
confidence: 99%
“…Kirsch et al analyzed the types and characteristics of public health emergencies, as well as the advantages of military hospitals in responding to public health emergencies, from strengthening military-civilian cooperation, strengthening military-civilian collaboration, and strengthening military hospitals' ability to respond to public health emergencies. It discusses and provides a reference for establishing the army's emergency response mechanism in the future [8].…”
Section: Introductionmentioning
confidence: 99%